Correlation of Prolonged Total Ischemic Time with Body Mass Index in Kidney Transplant: A Single Center Report - Eriawan Agung Nugroho; Erwin Wibowo; Prathita Amanda Aryani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Chronic kidney disease (CKD) is a rising health concern worldwide, especially in Indonesia. The treatment of choice for end-stage renal disease is Kidney Transplantation.1 Numerous studies showed that prolonged total ischemic ischemic time may cause hypoxia of the graft tissue and increased risk of ischemia and reperfusion injury (IRI) and delayed graft function (DGF).2 Body mass index of kidney transplant recipients may cause prolonged duration of the procedure, as well as prolonged total ischemic time. This study aimed to determine the correlation between prolonged total ischemic time with body mass index. Method: This was an observational and cross-sectional analysis at Kariadi General Hospital Semarang involving patients who underwent kidney transplantation from January 2016 to December 2019. The total ischemic time was recorded intraoperatively. The Body Mass Index data were provided by medical records. The program used to statistically analyze the data was SPSS 23.0, and Spearman was used for hypothesis testing. Result: This study included 25 kidney transplant recipients. The mean total ischemic time was 43,27 ± 6,63 minutes. There was a significant positive correlation between prolonged ischemic time and body mass index (r= 0,506 ; p= 0,010). Conclusion: Prolonged total ischemic time was positively correlated with increased body mass index and these results are statistically significant.